Report on public health actions and vaccination strategies to monitor measles epidemic in Local Health Unit A in Rome, Italy (Italian Journal of Public Health, 2012)
Background: Between May 2010 and october 2011 the unit of Preventive Medicine for thedevelopmental ages of district IV, Health unit aSL rM/a, received 136 measles case notifications fromthe unit of Epidemiology and Prophylaxis of Infectious diseases.MEtHodS: In accordance with the infectious diseases monitoring protocol, we introduced a series ofpreventive measures, such as monitoring subjects in contact with measles-infected patients, recommend-ing the administration of two Measles Mumps and rubella (MMr) doses four weeks apart, and informingpaediatricians, families and school teachers about the measles epidemic.rESuLtS: all the activities above led to an increased number of MMr doses administered and a significantimprovement of measles immunization coverage among residents of the district IV health unit of rome.concerning MMr 1, in a sample cohort consisting of children ≤24 months, the immunization coverageincreased from 77% on the 31/12/09 to 88% on the 31/12/11. Instead, for MMr 2, in a cohort of children≤6 years, the same ratio improved from 51% on the 31/12/09 to 65% on the 31/12/11.dIScuSSIon: the results indicate a material increase in the immunization coverage once our public healthactions and vaccination strategies had been implemented among young residents of district IV aSL rM/a.
Keywords: Measles; Vaccination; Public health; Monitoring